Gender-Smart Accelerator Challenge results and recommendations for improving access to finance as well as improving resilience for women-led small and medium entreprises in agri-food systems - Derenoncourt, Marie Ena; Jaquet, Stephanie (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This is the poster that was accepted for presentation at the CGIAR Gender Impact Platform international conference ‘From research to impact: Towards just and resilient agri-food systems’ that took place in New Delhi, India, from 9-12 October 2023.